2022
DOI: 10.1525/elementa.2022.00080
|View full text |Cite
|
Sign up to set email alerts
|

Single-blind determination of methane detection limits and quantification accuracy using aircraft-based LiDAR

Abstract: Methane detection limits, emission rate quantification accuracy, and potential cross-species interference are assessed for Bridger Photonics’ Gas Mapping LiDAR (GML) system utilizing data collected during laboratory testing and single-blind controlled release testing. Laboratory testing identified no significant interference in the path-integrated methane measurement from the gas species tested (ethylene, ethane, propane, n-butane, i-butane, and carbon dioxide). The controlled release study, comprised of 650 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 12 publications
2
43
0
Order By: Relevance
“…Using the probability of detection and uncertainty models of Conrad et al derived through parallel controlled release studies in Saskatchewan, detection sensitivities during the present flights were 0.3–1.8 kg/h (at 50% probability of detection) with single- and multipass measurement uncertainties of −65/+141% and −41/+63%, respectively. These uncertainties are consistent with those found in tests by Bell et al This detection limit is near the 1 kg/h threshold suggested as sufficient to capture all significant methane sources at upstream oil and gas facilities . Manual review of high-definition photography captured from the plane permitted detected emissions to be associated with specific emitting infrastructure on each site.…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…Using the probability of detection and uncertainty models of Conrad et al derived through parallel controlled release studies in Saskatchewan, detection sensitivities during the present flights were 0.3–1.8 kg/h (at 50% probability of detection) with single- and multipass measurement uncertainties of −65/+141% and −41/+63%, respectively. These uncertainties are consistent with those found in tests by Bell et al This detection limit is near the 1 kg/h threshold suggested as sufficient to capture all significant methane sources at upstream oil and gas facilities . Manual review of high-definition photography captured from the plane permitted detected emissions to be associated with specific emitting infrastructure on each site.…”
Section: Methodsmentioning
confidence: 92%
“…Bridger Photonics' GML is an aircraft-mounted LiDAR and camera system that leverages Wavelength Modulation Spectroscopy (WMS) to detect methane plumes between the plane and the ground and produce geolocated plume imagery at 1−2 m resolution. A detected plume's path-integrated methane 34 This detection limit is near the 1 kg/h threshold suggested as sufficient to capture all significant methane sources at upstream oil and gas facilities. 35 Manual review of high-definition photography captured from the plane permitted detected emissions to be associated with specific emitting infrastructure on each site.…”
Section: Methodsmentioning
confidence: 92%
“…The Fugitive Emissions Abatement Simulation Tool or FEAST uses a monte-carlo based approach to model the evolution of methane emissions and the effectiveness of leak detection and repair programs at oil and gas facilities (14,15). In brief, FEAST takes as inputs data on performance parameters of leak detection technologies obtained through controlled release tests and field trials (1,2,4,(20)(21)(22). The activity data for oil and gas facilities, including component and equipment counts, is taken from the EPA supplemental proposal -only Model Plant 4, representing well sites with major production and processing equipment and centralized production facilities, is included in this study (13).…”
Section: Feast Simulation Set Upmentioning
confidence: 99%
“…New technologies such as aerial systems, drones, satellites, and continuous monitoring systems (CMS) promise faster and more cost-effective methane mitigation compared to conventional optical gas imaging (OGI) surveys. These new technologies have been extensively tested under controlled release conditions to evaluate performance parameters such as probability of detection curves and quantification accuracy (1)(2)(3)(4). As a result, several operators are now deploying these technologies for cost-effective leak detection and mitigation (5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Bell et al 31 performed controlled testing with Solution 1 to assess the quantication accuracy and detection limits. The dataset included 650 individual measurement passes.…”
Section: Solution Uncertaintymentioning
confidence: 99%